THE USE OF THE COMBINATION OF FTIR, PYRIDINE ADSORPTION, 27Al AND 29Si MAS NMR TO DETERMINE THE BRÖNSTED AND LEWIS ACIDIC SITES (Jurnal Teknologi (Sciences & Engineering), 2016)
Lewis and Brönsted acidity were studied on ZSM-5 with combination of pyridine adsorption and FTIR vibration, ZSM-5 synthesized using kaolin Bangka Indonesia with an increase in the molar ratio of Si/Al 30-60 without pre-treatment and without organic templates and with seeds silicalite. Interestingly, the intensity of the infrared showed an increase of band vibration pyridine as absorbed Brönsted and Lewis acid sites in a molar ratio increase of Si/Al in ZSM-5, indicating an increase in the number of silanol (Brönsted acid) and deformed silica (Lewis acid) because the amount of Aluminum in ZSM-5 decrease with increase Si/Al but amount acidity increase. 29Si and 27Al MAS NMR analysis was supported by the results of infrared to indicate that all of the aluminum atom is coordinated with their neighbors are the same in ordering the ZSM-5 framework and 27Al MAS NMR showed a sharp peak of all the variations of Si/Al except the Si/Al 30 shows a low peak area. XRD analysis supported that the ZSM-5 structure formed is pure and crystal and a decrease in crystallinity proven for more than Si/Al 50, that defects silica occurs in ZSM-5, this corresponds to the growing number of Lewis acid sites caused by defects silica described the infrared results.